1994
DOI: 10.1055/s-2006-959439
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of aPythiumElicitor Treatment on the Growth and Alkaloid Production ofCatharanthus roseusCell Suspensions

Abstract: The treatment of a CATHARANTHUS ROSEUS cell suspension culture with a low concentration of PYTHIUM elicitor stimulated the alkaloid production. When these pretreated cells were resuspended in a medium that did not contain the fungal extract, the positive effects of the treatment on alkaloid synthesis and excretion were lost and, moreover, the standard level of production was not recovered. A second treatment of these cells with PYTHIUM elicitor at day 5 of the second culture cycle greatly impaired growth kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In this study, we observed that chitin at 250 mg L À1 caused a decrease in the L-DOPA content and even in PPO and tyrosinase activities, while at lower concentrations (200 mg L À1 ), it resulted in accumulation of more amount of L-DOPA and enzyme activities. This may be attributed to hypersensitive response leading to cell death, as reported by Nef-Campa, Trousot, Trouslot, and Chrestin (1994) and Rijhwani and Shanks (1998).…”
mentioning
confidence: 72%
“…In this study, we observed that chitin at 250 mg L À1 caused a decrease in the L-DOPA content and even in PPO and tyrosinase activities, while at lower concentrations (200 mg L À1 ), it resulted in accumulation of more amount of L-DOPA and enzyme activities. This may be attributed to hypersensitive response leading to cell death, as reported by Nef-Campa, Trousot, Trouslot, and Chrestin (1994) and Rijhwani and Shanks (1998).…”
mentioning
confidence: 72%